THE DETERMINANTS OF INDONESIAN CRUDE PALM OIL EXPORT: GRAVITY MODEL APPROACH - Ridwannulloh, Ridwannulloh; Sunaryati, Sunaryati (Universitas Muhammadiyah Yogyakarta, 2018)
Crude Palm Oil (CPO) is a commodity in the agricultural sector with the largest contribution to the value of Indonesian exports. Moreover, since 2006, Indonesia has become the largest CPO producer in the world. Therefore, this research attempts to investigate determinants of Indonesia CPO export to main trading partners using Gravity model approach. This study is conducted to analyze the effect of Indonesia’s GDP, GDP of Indonesia’s four main trading partners, distance, the rupiah exchange rate against US dollar and domestic CPO consumption on Indonesian CPO exports. The analysis technique is used in this research is panel data regression using fixed-effect model. The results of this study indicate that not all variables have significant effect on Indonesian CPO exports. Variables such as Indonesia’s GDP and GDP of major trading partners have positive and significant effect, whereas rupiah exchange rate variable and domestic consumption have negative and significant effect on Indonesian CPO export. In addition, in line with Gravity model, variable of distance has negative and significant effect on Indonesian CPO exports.